Monomeric CRP is Elevated in Patients with COPD Compared to Non-COPD Control Persons - Munuswamy R (Dove Medical Press, 2021)
Revathy Munuswamy,1,* Jana De Brandt,2,* Chris Burtin,2 Wim Derave,3 Joseph Aumann,4 Martijn A Spruit,5,6,* Luc Michiels1,* 1Faculty of Medicine and Life Sciences, Biomedical Research Institute BIOMED, Hasselt University, Hasselt, Belgium; 2Faculty of Rehabilitation Sciences, Rehabilitation Research Center REVAL, Biomedical Research Institute BIOMED, Hasselt University, Hasselt, Belgium; 3Department of Movement and Sports Sciences, Ghent University, Ghent, Belgium; 4Department of Pneumology, Jessa Hospital, Hasselt, Belgium; 5Department of Research and Development, CIRO, Horn, the Netherlands; 6Department of Respiratory Medicine, Maastricht University Medical Centre, Faculty of Health, Medicine and Life Sciences, NUTRIM School of Nutrition and Translational Research in Metabolism, Maastricht, the Netherlands*These authors contributed equally to this workCorrespondence: Luc Michiels Email luc.michiels@uhasselt.beAbstract: Chronic low-grade systemic inflammation is frequently observed in patients with chronic obstructive pulmonary disease (COPD), e.g., elevated pentameric CRP (pCRP). However, pCRP can dissociate to form monomeric CRP (mCRP) which exhibits a clear pro-inflammatory behaviour in contrast to the more anti-inflammatory properties of pCRP. Therefore, mCRP may be an informative biomarker to demonstrate chronic low-grade systemic inflammation. This was confirmed by analysing serum samples from 38 patients with COPD and 18 non-COPD control persons (NCCP). mCRP was significantly elevated in patients with COPD vs. NCCP, indicating that mCRP might be considered as a new sensitive marker of chronic low-grade systemic inflammation.Keywords: COPD, low-grade systemic inflammation, pCRP, mCRP